DIAGNOSIS OF CANINE MELANOMA - de Morais, Dennis Mafra; Almeida, Amanda Beatriz de Andrade Bandeira Nunes; Ferreira, Caroline Gracielle Torres; Souza, Sarah Maria Oliveira (Seven Editora, 2026)
This study aimed to synthesize the main evidence on the diagnosis and staging of canine melanoma, with emphasis on histopathological, molecular, and prognostic advances. This is a narrative literature review, based on studies published between 2021 and 2025, selected from the PubMed and Google Scholar databases. The results demonstrated that the diagnosis of canine melanoma is no longer restricted to morphological evaluation, but now involves a multimodal approach based on cytology, histopathology, clinical staging, and biomarkers. It was found that diagnostic confirmation depends mainly on biopsy and histopathological evaluation, especially in poorly pigmented or amelanotic cases, which hinder the initial recognition of the neoplasm. In addition, TNM staging, associated with lymph node evaluation and thoracic imaging exams, proved essential for the detection of metastases and prognostic definition. Advances in the use of serum, genetic, and hypoxia-related biomarkers have also been identified, with the potential to aid in predicting metastatic behavior and therapeutic response. Therefore, it is concluded that the identification of the neoplastic cell alone is not sufficient for the diagnosis of canine melanoma; evaluation of tumor biological behavior is necessary for better prognostic and therapeutic guidance.